Diagnóstico de la gestión pública del territorio costero del País Vasco - Santos-Ellakuria, Ibone (Geographicalia, 2019)
Coastal zones have special relevance in spatial planning due to their socioeconomic and environmental importance and their exposure to the impacts of human activities and natural risks. The objective of integrated coastal zone management (ICZM) is the sustainable development of coastal zones, integrating sectoral policies and the coastal and marine components of the coast. A diagnosis of the legal administrative framework of the management of the Basque Country is made, in order to detect those dysfunctions that are needed to correct to develop an ICZM policy. The diagnosis is made through the analysis of policies, current regulations, administrative competences, planning instruments, training programs, degree of knowledge of the environment and mechanisms of participation in decision making. It is concluded that to develop a regional ICZM policy, it is necessary to increase the integration and coordination of sectoral policies and improve governance.